A new attenuated and highly immunogenic orthopoxvirus vaccine protects against mpox in mice and macaques - Fengwen Xu; Yu Huang; Yongzhi Hou; Yu Xie; Baoying Huang; Fei Zhao; Zhao Gao; Chen Chen; Jiaxun Wang; Shan Mei; Yamei Hu; Liming Wang; et al. (npj Vaccines)
Abstract Shortly after 2022, mpox again becomes a public health emergency of international concern as declared by the World Health Organization on August 14, 2024. Smallpox vaccines ACAM2000 and MVA-BN were approved for mpox prevention in several countries. However, the side effects of ACAM2000 and the limited supply of MVA call for the development of new mpox vaccines to prevent mpox and other orthopoxvirus infections. In this study, we engineered a new generation of attenuated and highly immunogenic vaccinia virus named dBTF based on the vaccinia Tiantan strain which is a replication-competent smallpox vaccine widely used in China. The dBTF vaccinia virus is impaired in replication and low in virulence, induces strong vaccinia virus-specific humoral and cellular immune responses. Importantly, single dose of dBTF vaccination effectively protects mice and cynomolgus macaques from mpox virus challenge. These results support the development of dBTF into a new generation of mpox and orthopoxvirus vaccines.